Microwave ablation induces Th1-type immune response with activation of ICOS pathway in early-stage breast cancer. Issue 4 (1st April 2021) - Zhou, Wenbin; Yu, Muxin; Pan, Hong; Qiu, Wen; Wang, Hui; Qian, Mengjia; Che, Nan; Zhang, Kai; Mao, Xinrui; Li, Li; Wang, Ruoxi; Xie, Hui; et al.
Abstract : Background: Despite great advances in the treatment of breast cancer, innovative approaches are still needed to reduce metastasis. As a minimally invasive local therapy (not standard therapy for breast cancer), microwave ablation (MWA) has been attempted to treat breast cancer, but the local effect and immune response induced by MWA have seldom been reported. Methods: The clinical study was performed to determine the complete ablation rate of MWA for early-stage breast cancer. Secondary endpoints included safety and antitumor immune response. 35 subjects from this clinical study were enrolled in the current report, and the local effect was determined by pathological examinations or follow-up. To investigate MWA-induced immune response, patients treated with surgery (n=13) were enrolled as control, and blood samples were collected before and after MWA or surgery. The immune cell populations, serum cytokines, secretory immune checkpoint molecules, and T-cell receptor sequencing were analyzed. Results: Of 35 enrolled patients, 32 (91.4%) showed complete ablation. Compared with surgery, MWA induced significantly increased levels of inducible co-stimulator (ICOS)+ activated CD4+ T cells and serum interferon gamma, indicating a shift in the Th1/Th2 balance toward Th1. The activated ICOS pathway was involved in the MWA-induced adaptive immune response. T-cell receptor sequencing revealed MWA of primary tumor activated T lymphocytes expansion and recognized some cancer-specific antigens. Moreover, CD4+ effector memory T-cell response was induced by MWA, and the immune response still existed after surgical resection of the ablated tumor. Conclusions: MWA may not only be a promising local therapy but also a trigger of antitumor immunity for breast cancer, opening new avenues for the treatment of breast cancer. Combinatorial strategy using additional agents which boost MWA-induced immune response could be considered as potential treatment for clinical study for early breast cancer therapy.